BIAYA DAN PRODUKTIVITAS TREE LENGTH LOGGING DI HUTAN ALAM PRODUKSI - Idris, Maman Mansyur; Sukanda, Sukanda (Jurnal Penelitian Hasil Hutan, 2012)
This study examined cost and productivity of tree length logging system in natural production forest. The study was conducted in several forest concession in Kalimantan. The results showed that the sytem is capable to extract the clearbole part as main production log and the wasted log above the first branch into the landing point. Skidding productivityof tree length syistem in PT Gunung Gajah Abadi 6,25 m3/jam/hm, PT Narkata Rimba 15,54 m3/hr/hm, PT Balikpapan Forest Industries 16,67 m3/hr/hm, PT Jatitrin Co Ltd 20,76 m3/hr/hm, PT Dwima Jaya Utama 36,69 m3/hr/hm dan PT Kayu Tribuana Rama 21,67 m3/hr/hm.The average cost of tree length logging system in PT Gunung Gajah Abadi is Rp 84.817,92 / m3, PT Narkata Rimba Rp 33.636,55/ m3, PT Balikpapan Forest Industries Rp 31.800,34/ m3, PT Jatitrin Co Ltd Rp. 25.535,26/ m3, PT Dmimajaya Utama Rp 14.155,19/ m3 and PT Kayu Tribuana Rama Rp. 25.207,41/ m3.